Fault‐tolerant permanent magnet synchronous machine – phase, pole and slot number selection criterion based on inductance calculation. Issue 2 (1st February 2015) - Prieto, Borja; Martínez‐Iturralde, Miguel; Fontán, Luis; Elosegui, Ibon
Abstract : Interest in permanent magnet synchronous machines for safety‐critical applications has been increasing over the years. One of the most common methods for providing fault tolerance to a permanent magnet machine is the active control from the drive side. This method requires designing machines with the lowest possible mutual coupling between phases and a self‐inductance that is high enough to limit the fault currents. Fractional‐slot concentrated windings have been proposed as the most advantageous solution to meet these requirements. When comparing the numerous combinations of phases, poles and slots that give rise to a fractional‐slot concentrated winding, the usual criteria only focus on obtaining a single‐layer winding and do not actually consider the relationship between the self‐inductance and the mutual inductance between phases. Moreover, they give no recommendations regarding the optimal number of phases from a magnetic point of view. The present work aims to cover this gap by obtaining analytical expressions for the calculation of the inductances in a permanent magnet machine. The derived expressions are investigated regardless of the geometry of the machine, and the criteria for selecting the most promising combinations in terms of the machine's fault tolerance are extracted.